Struktur Sintaksis dan Distribusi Jenis Klausa pada Lirik Lagu Album Rahasia Pertama Karya Rony Parulian - Nisha Marsha Shonia; Aditya Ansor Alsunah; Lina Siti Nurwahidah; Cecep Dudung Julianto (Asosiasi Ide Bahasa Kepri, 2025)
Song lyrics constitute a distinctive form of literary expression in which linguistic structure plays a crucial role in shaping meaning and emotional resonance. This study examines the syntactic structure and distribution of clause types in the song lyrics of Rahasia Pertama, the debut album by Rony Parulian. The research focuses on identifying and classifying clause types that appear in the lyrics, namely verbal clauses, nominal clauses, adjectival clauses, prepositional clauses, and numeral clauses, based on their formal characteristics and syntactic functions. Employing a descriptive qualitative method, the data were obtained through careful reading and systematic note-taking of the lyrics from all eight songs in the album. The collected data were then categorized and interpreted according to established syntactic theories. The findings reveal a total of 213 clauses distributed across four clause types: verbal clauses, nominal clauses, adjectival clauses, and prepositional clauses. Verbal clauses are the most dominant, indicating that the lyrics predominantly emphasize actions, processes, and emotional dynamics experienced by the lyrical subject. Nominal and adjectival clauses function to express states, identities, and emotional qualities, while prepositional clauses contribute metaphorical spatial and emotional nuances. Notably, numeral clauses are entirely absent from the album, suggesting that numerical expressions are not central to the construction of meaning in these song lyrics. These results demonstrate that syntactic structure significantly contributes to the expressive and poetic power of song lyrics. Through varied clause constructions, the album conveys themes of love, longing, loss, and emotional endurance in a nuanced manner. This study highlights the importance of syntactic examination in understanding how popular song lyrics function as literary texts and affirms the relevance of linguistic analysis in contemporary literary and cultural studies.